Synthesis and application of nano-silicon prepared from rice husk with the hydrothermal method and its use for anode lithium-ion batteries - Susilo Sudarman; Andriayani; Tamrin; Muhammad Taufik (Materials Science for Energy Technologies, 2024)
Nano-silicon is synthesized by hydrothermal method from rice husk, which has the advantage of using low temperature in an autoclave at 180 °C. Reduction of silica using a mixture of silica gel extracted from rice husks with Mg powder. The silica gel and Mg powder reaction produces nano-silicon. XRD diffractogram, it can be seen that Si-0.5, Si-0.6, and Si-0.7 form hkl (111), (220), (311), (400), (331), and (422). Raman spectra show peaks at the Raman shift of 520 cm−1, XPS spectrum high scan Si2p peaks at 99 eV, indicating silicon, and at 103 eV, the oxide layer on nano-silicon. The isotherm adsorption graph using the BET method type IV isotherm graphs with surface areas are 18.60 m2g−1 until 20.39 m2g−1. Pore size using the BJH method shows 1.69 nm until 8.30 nm. SEM and TEM nano-silicon morphology images, the shape of the nano-silicon is spherical. The nano-silicon formed produces high-performance anode lithium-ion batteries with a discharge capacity of 1757 mAh g−1, above 1000 mAh g−1 for approximately 200 cycles.